PENGARUH EKSTRAK KAYU SECANG (Caesalpinia sappan L) TERHADAP VIABILITAS SPERMATOZOA MENCIT JANTAN (Mus musculus L) - Rusmiati Rusmiati (Universitas Lambung Mangkurat, 2007)
The low participation of men in Family Planning Program is caused by the limited choices of contraception for men. The purpose of this research is to find out the effects of secang woods extract on the spermatozoa viability of male mice, it is expected that some day secang wood could be formulated into components of oral contraception for male. Thirty male mice weigh 25-30 g of 2,5 month old are grouped using Complete Random Design (RAL) factorial patterned 2x5 witn n=3. The extract of secang wood is made as ethanol extract, chloroform and water fraction each with 50 mg/25 g weight and given 1 ml orally each day. The analysis of the spermatozoa viability is conducted by supravital painting. The observation of preparation is done by 400x magnification. The living spermatozoa are colorless and the dead ones are red. The observation is conducted twice. Ten days after the extract is given (to identify the changes) and ten days after the extraααct is stopped (to see the recovery of spermatozoa). The gathered data is tested using Anava (α = 0,05) and DMRT (α = 0,05). The result shows that the extract of secang wood can lower the viability of mice spermatozoa.